2020
DOI: 10.1186/s12935-020-01376-8
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA ANRIL/miR-7-5p/TCF4 axis contributes to the progression of T cell acute lymphoblastic leukemia

Abstract: Background Antisense non-coding RNA in the INK4 locus (ANRIL) is of great importance in cell biological behaviors, and ANRIL functions in many kinds of cancers including leukemia. However, the mechanism of ANRIL in the progression of T-cell acute lymphoblastic leukemia (T-ALL) has not been clarified clearly. Methods qRT-PCR was performed to detect ANRIL expression in T-ALL samples. T-ALL cell lines (MOLT4, CCRF-CEM and KOPT-K1) were used as the cell models. The function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…Shu et al have reported that silence of ANRIL exacerbates H9c2 cell injury induced by hypoxia by miR-7-5p/SIRT1 axis [27]. Li et al have revealed that ANRIL mediates the migration and invasion of T-cell acute lymphoblastic leukemia via miR-7-5p/TCF4 axis [28]. In our study, we also veri ed that ANRIL sponge to miR-7 through dualluciferase reporter assay.…”
Section: Discussionsupporting
confidence: 74%
“…Shu et al have reported that silence of ANRIL exacerbates H9c2 cell injury induced by hypoxia by miR-7-5p/SIRT1 axis [27]. Li et al have revealed that ANRIL mediates the migration and invasion of T-cell acute lymphoblastic leukemia via miR-7-5p/TCF4 axis [28]. In our study, we also veri ed that ANRIL sponge to miR-7 through dualluciferase reporter assay.…”
Section: Discussionsupporting
confidence: 74%
“…Besides this, there are many lncRNAs located both in the cytoplasm and nucleus, and act as sponges for microRNAs, such as lncRNA ANRIL. [44] In our study, we found that LINC00511 regulated Wnt/β-catenin signaling by sponging miR-126-5p. Indeed, LINC00511 has been reported to regulate the proliferation and apoptosis of bladder cancer cells via Wnt/β-catenin signaling.…”
Section: Of 16mentioning
confidence: 49%
“…Besides this, there are many lncRNAs located both in the cytoplasm and nucleus, and act as sponges for microRNAs, such as lncRNA ANRIL. [ 44 ]…”
Section: Discussionmentioning
confidence: 99%
“…T-cell acute lymphoblastic leukemias (T-ALL) is a common hematological malignant tumor in children, accounting for 80% of childhood leukemia cases, and it is also the second most common acute leukemia in adults. [4,5] In the past 20 years, the complete remission rate of initial treatment has remained low, while the fatality rate was high. [6] The 5-year survival rate is about 30% for adults and about 90% for children.…”
Section: Introductionmentioning
confidence: 99%